Analisis kandungan gizi, kadar magnesium, & kalium bolu kukus berbasis tepung biji kecipir dan tepung pati garut sebagai inovasi produk sport food - Sahirah Aliyah Firdaus; Nanang Nasrulloh (Poltekkes Kemenkes Aceh, 2026)
Background: Exercise-associated muscle cramps (EAMC) in athletes are associated with fluid and electrolyte loss during intense physical activity. Therefore, sports nutrition that supports adequate intake of macronutrients and essential minerals is necessary. Winged beans have potential as a source of protein and minerals, and arrowroot flour can serve as an alternative source of carbohydrates for developing sports foods.Objectives: To develop steamed cake products based on winged bean flour and arrowroot starch as local sports food innovations and analyze their nutritional composition, magnesium and potassium levels, and organoleptic properties.Methods: This experimental study used a completely randomized design with variations in the proportions of winged bean flour and arrowroot flour in three formulations: F1 (25%:75%), F2 (50%:50%), and F3 (75%:25%). The proximate composition and mineral content were analyzed at the Saraswanti Indo Genetech Laboratory, Bogor, while the organoleptic evaluation was conducted using a nine-point hedonic scale by 30 semi-trained panelists. The data were analyzed using ANOVA, Duncan's Multiple Range Test, and DeGarmo’s Method.Results: Significant differences (p<0.05) were observed among the formulations with respect to energy, protein, carbohydrate, fat, ash, magnesium, and potassium content. Formulation F3 was selected as the best owing to its superior nutritional quality, with higher protein and electrolyte mineral levels; however, organoleptic testing showed that F1 had the highest sensory acceptance level. Conclusion: The steamed cake made from winged bean flour and arrowroot starch (F3) has potential as a local sports food rich in protein and essential minerals to support energy, muscle function, and electrolyte balance in athletes.